Media Pembelajaran Perubahan Fisik dan Psikologis pada Kehamilan Berbasis Android pada Masa Pandemi Covid-19 - Yulia Sartika; Syafruddin Syarif; Sri Ramadany (Jurnal Bidan Cerdas, 2022)
Introduction:There is a need for innovations that are needed by teaching staff in improving students' abilities, especially in mastering the material on Physical and Psychological Changes in pregnancy in the Pregnancy Midwifery Care course. Research objectives: To produce android-based pregnancy care learning media in increasing student knowledge about physical and psychological changes in pregnancy. Research Methods: Designing this application using Research and Development (R&D) and assessing the level of student knowledge using Pre-experimental (one group pre test and post test design) totaling 34 students. Data analysis in this study used descriptive statistics analysis and McNemar test. Results: The study showed that the assessment of learning media in the material expert validation test obtained a score (95%) with a very decent category. The media expert validation (92.5%) was categorized as very feasible. The assessment of media usability using the Technology Acceptance Model (TAM) questionnaire by assessing aspects of convenience, usability, trust, user intentions and user attitudes is categorized as good. Based on the results of the statistical test of knowledge before and after being given android-based learning media, there was a significant difference in knowledge of 47.06% with a p value <α where 0.00 <0.05. Conclusion: Android-based learning media for midwifery care is feasible and effective in increasing the knowledge of midwifery students in mastering the material of physical and psychological changes.